2013
DOI: 10.1080/10549811.2013.807745
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Seed Germination inTrema orientalis(L.) Blume—Potential Plant Species in Revegetation of Mine Wastelands

Abstract: Natural forest succession takes a long time to accumulate sufficient nutrients to support plant growth and enhance soil microbial activity. Human intervention in selecting native pioneer plant species is therefore required to accelerate sustainable restoration. Trema orientalis (L.) Blume, a fast growing pioneer plant species, has the ability to grow in nutrient deficient soils and proves to have reclamation potential in mine wastelands. However, its use has been limited due to low germination percentages and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Inoculation with AM fungi has been found to enhance the growth of seedlings of several fruit crops and has helped to achieve high production levels (Rodrigues and Rodrigues, 2014). In our study, we tested the effects of inoculation with five different AMF species on the early vegetative development of persimmon seedlings under sterile sandy soil conditions of Brazil, this being the first report on persimmon inoculation in that country.…”
Section: Discussionmentioning
confidence: 99%
“…Inoculation with AM fungi has been found to enhance the growth of seedlings of several fruit crops and has helped to achieve high production levels (Rodrigues and Rodrigues, 2014). In our study, we tested the effects of inoculation with five different AMF species on the early vegetative development of persimmon seedlings under sterile sandy soil conditions of Brazil, this being the first report on persimmon inoculation in that country.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the highest growth uniformity of 74.75 % and 72 % before storage and after storage respectively was obtained by subjecting T. orientale seeds to a hydrated-dehydrated procedure [ 99 ]. Studies by Rodrigues and Rodrigues [ 101 ], indicated the potential of enhancing the seeds of T . orientale through different pre-treatment options.…”
Section: Domestication Potentialmentioning
confidence: 99%
“…The drupes of T. orientalis are bird feeding [70], and the seeds are suborthodox [71] and are commonly found in the soil seed banks in low-elevation forests in Taiwan [3,16,[20][21][22]30,52]. T. orientalis is also a fast-growing pioneer species common after forest disturbances in tropical forests in Asia [2,[72][73][74][75], and is a species with forest restoration potential [76]. In the Trema orientalis type at Dadu Terrace, due to the presence of T. orientalis parent trees and the fact that T. orientalis seeds need to be stimulated by variable temperature or light to break dormancy and germinate out of the soil [68], T. orientalis seeds can continuously accumulate in the soil seed bank under the shade of their parent tree.…”
Section: Feasibility Of Soil Seed Banks For Vegetation Restorationmentioning
confidence: 99%